Matematyka
Matis2012
2017-09-29 23:03:55
Zadanie w załączniku
Odpowiedź
princcccessssss
2017-09-30 05:57:52

a) A = (3a-8, 2b+3), B = (b+4, a-1) -(3a-8)=b+4 -(2b+3)=a-1 -3a+8=b+4 -2b-3=a-1 b=-3a+4 6a-8-3=a-1 b=-3a+4 5a=10 a=2 b=-2 A=(-2,-1), B=(2,1) b) A = (2a+3b+2½, a/2-b/3), B = [(a-b)/2, a-b - 1⅓)] -(2a+3b+2½)=(a-b)/2 -(a/2-b/3)=a-b - 1⅓ -2a-3b-2,5=0,5a-0,5b -0,5a+⅓b=a-b-1⅓ 2,5a+2,5b=-2,5 4,5a-4=4b a+b=-1 b=1,125a-1 2,125a-1=-1 2,125a=0 a=0 b=-1 b) A = (-½, ⅓), B = (½,-⅓)

Dodaj swoją odpowiedź